Studi Komposisi Jenis Sampah Pesisir pada Lokasi Wisata Alam di Pulau Lombok - Jumiarti; Waspodo, Saptono; Larasati, Chandrika Eka (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2023)
Water characteristics such as currents at Sedayu Beach, Penghulu Agung Beach, and Kuranji Beach have a role in transporting marine waste. Likewise, with the ebb and flow of sea water, the tides will bring marine waste towards the coast so that a lot of rubbish will accumulate on the coast. The dominant type of rubbish is plastic rubbish, which is the type of sea rubbish that is most commonly found on Kuranji Beach at 0.64 pcs/m², for Penghulu Agung Beach. as much as 0.84 pcs/m², and Sedayu Beach as much as 7.4 pcs/m², of the total three marine waste reports from research results related to types of marine waste in Indonesia itself, the composition of plastic waste has continued to increase by 5-6% since 2000. According to data from the Plastics Industry Association Indonesia and the Central Statistics Agency in 2018, plastic waste in Indonesia reached 64 million tons per year, and 3.2 million tons of it was thrown into the sea.